Treatment and Screening of Diabetic Retinopathy at Community Hospital Amnat Charoen Province, 2009 - Mujarin, Boodsanee; Jumnoonsiri, Uraiwan; Burat, Dokbua; Srengbun, Potjanee; Ponchana, Juraluk; Wechakama, Janchay (Journal of Health Science of Thailand, 2017)
Diabetic retinopathy is the most frequent cause of visual loss and poor quality of life in diabetic mellitus patients. In Amnat Charoen province, the number of person with diabetic mellitus in 2008 was 9,567 persons; of these only 10 percent were screened for diabetic retinopathy. Some diabetic mellitus patients developed blindness because of limited number of ophthalmologists and patients who required more advanced treatment were referred to other ophthalmologist in a tertiary hospital. This descriptive study was conducted by screening diabetes patients in community hospitals in Amnat Chareon province with an objective to study the screening and treatment of diabetic retinopathy in the province using fundus cameras. All of 7,366 diabetes patients in six community hospitals were screened in 2009. The fundi of diabetes patients were captured using non-mydriatic digital fundus cameras, by trained nurses. All of fundus images were interpreted by an ophthalmologist and patients who had severe non-proliferative diabetic retinopathy were treated with laser. Data were analyzed by descriptive statistics. Only 71.23 percent of the diabetes patients were screened. The prevalence of diabetic retinopathy were 23.42 percent, mild NPDR 20.83 percent, moderate NPDR 1.88 percent and severe NPDR 0.77 percent. Cataract prevalence was 6.27 percent and other eye complications 0.8 percent whereas 37.83 percent of diabetes patients with severe NPDR were treated by laser at the center of screening treatment, Lue Amnat hospital. The beneficial effect of this diabetic retinopathy screening are diabetes patients can be assessed annually in the screening and should be treated deter to permanant visual loss. In so doing, related cost and loss are reduced while patients’ satisfication increases. Such program will be most appropriate for remote rural areas without any ophthalmologist or with limited number of the specialist.